Adapt or die: a competitive digital supply chain quality management strategy - Yogesh Dwivedi (Journal of Enterprise Information Management, 2024)
Purpose – The evolution of modern digitalization technologies necessitates the development of a competitive digital supply chain quality management (SCQM) strategy by manufacturers. Using the new institutions and institutional theory (IIT), the study research first aims to identify the most important SCQM practices that can influence competitive performance (CP). Second, the authors intend to investigate the role of digital strategy alignment (DSA) in moderating the relationship between the multidimensionality of SCQM practices and CP among manufacturers. Design/methodology/approach – The authors employ the Partial Least Squares-Structural Equation Modeling (PLS-SEM) technique to examine 225 valid samples from Malaysian manufacturers who use SCQM practices. Findings – The study findings indicate that five of the twelve hypotheses developed were accepted. This suggests that supplier focus, strategic collaboration, information sharing and customer focus are positively and significantly correlated with CP. Unexpectedly, DSA moderates the relationship between leadership and CP. Originality/value – This study extended the new IIT by empirically testing the six SCQM practices for CP in a DSA context, which can serve as a model for future research in the SCQM, CP and DS fields.